Factors that influence individuals' intention to adopt blockchain in banking institutions in Malaysia / Wang Ruixui ... [et al.] - Wang, Ruixui; Wu, Yahui; Zainordin, Nur Aqilah; Izni, Nor Aziyatul; Annuar, Nursyamilah (Universiti Teknologi MARA, Perlis, 2023)
The industry of blockchain technology has become more and more important with the rapid development of the financial industry. Blockchain technology in many developed countries is relatively mature, and Malaysia still has a large blockchain market compared to it. The main purpose of this research is to study factors that influence individuals to adopt blockchain in banking institutions in Malaysia. Through the Unified Theory of Technology Acceptance and Use Technology (UTAUT) theory, this study determines the relationship between effort expectancy, performance expectancy, enabling conditions, and social influence on an individual's behavioral intention to adopt blockchain. A survey of 300 participants was carried out by distributing questionnaires via social media platforms. The results were analyzed using SPSS to test factor analysis, reliability, Pearson correlation analysis, and multiple linear regression analysis. The findings revealed that all; effort expectancy, performance expectancy, enabling conditions, and social influence, have direct relationships with blockchain behavior intention in Malaysia.